Osteoporosis Awareness in Asthma Patients Using Inhaled Corticosteroids: A Cross-Sectional Study - Sevda Cömert; İlknur Aktaş; Feyza Ünlü Özkan; Duygu Silte Karamanlioglu; Pinar Akpınar; Serap Diktaş Tahtasakal; Berrin Zinnet Eraslan; Gülcan Öztürk (Sakarya Tıp Dergisi)
Objective: The aim of this study was to assess osteoporosis awareness in asthma patients using inhaled corticosteroids (ICS) and to identify the influencing factors.Materials and Methods: A total of 109 asthma patients using ICS (10 male, 99 female; mean age: 50.30±12.04 years) were included in the cross-sectional study. Demographic data regarding age, gender, education level, marital status, occupation and disease duration of all participants were recorded. General knowledge questions about osteoporosis, diet and exercise were asked. Osteoporosis awareness was assessed using the Osteoporosis Awareness Scale (OAS).Results: Osteoporosis awareness in asthma patients using ICS were found to be low. Eight of the participants included in the study (7.3%) were aware that they were at risk for osteoporosis, while 101 (92.7%) were unaware. The total OAS score was 51.32±15.70. The sub-score risk factor scores in postmenopausal women were significantly higher than those in premenopausal women (p< 0.05). The exercise, preventive behaviour, risk factor scores, the characteristics of OP scores and total score of participants who had heard of osteoporosis were statistically significantly higher than those who had not heard of it (p<0.05). The proportion of participants who had not heard of osteoporosis and were primary school graduates was significantly higher (68.1%) compared to those who had heard of osteoporosis (38.7%). The sub-score risk factor and preventive behavior scores were significantly higher for participants taking vitamin D compared to those not taking it (p<0.05). Additionally, the total and sub-score characteristics of OP, along with risk factor scores, were significantly higher in participants with a family history of fractures (p<0.05).Conclusions: Asthma patients using ICS have low levels of osteoporosis awareness. The menopausal status, vitamin D intake, family history of fractures and having heard OP before affects the osteoporosis awareness. In order to reduce the incidence of osteoporosis, morbidity and mortality, patient education programs should be organized especially for asthma patients especially using ICS in the risk group.